African Development Indicators 2002 (the international bank for reconstruction and development, 2002)
This volume presents data from 53 African countries, arranged in separate tables or matrices for more than 500 development indicators. The indicators are grouped into 14 chapters: background data, national accounts, prices and exchange rates, money and banking, the external sector, external debt and related flows, government finance, agriculture, power, communications and transportation, public enterprises, labor force and employment, aid flows, social indicators, and environmental indicators. Each chapter begins with a brief introduction on the nature of the data and their limitations, followed by a set of charts, statistical tables, and technical notes that define the indicators and identify their specific source.